Most active and interactive technologies foreign language teaching of students in the field of agricultural complex - Chornobai, Vira; Чорнобай, Віра Георгіївна (Причорноморський науково-дослідний інститут економіки та інновацій, 2020)
The problem of choosing the most effective and rational methods of teaching foreign languages that meet modern teaching conditions and meet the requirements of the standards of modern education has not lost its relevance for many decades. Interactive technologies allow students to play various personal and official roles in the training and playing field, to master them when creating a future model of human interaction in a production situation. When using interactive technologies in teaching, the student is as close as possible to the conditions of the educational material, is included in the situation being studied, is encouraged to take active actions, experiences a state of success and motivates his behavior. Проблема вибору максимально ефективних і раціональних методів викладання іноземних мов, які відповідають сучасним умовам навчання і вимогам стандартів сучасної освіти, не втрачає своєї актуальності протягом багатьох десятиліть. Інтерактивні технології дозволяють слухачам в навчально-ігровому полі програти різні особистісні та посадові ролі, засвоїти їх при створенні майбутньої моделі людської взаємодії у виробничій ситуації. При застосуванні в навчанні інтерактивних технологій студент максимально наближений до умов навчального матеріалу, включається в досліджувану ситуацію, збуджується до активних дій, переживає стан успіху і мотивує свою поведінку.
Найуживаніші активні та інтерактивні технології навчання іноземних мов студентів у сфері агропромислового комплексу
Keywords: interactive technologies; інтерактивні технології; active technologies; активні технології; pedagogical science; наука педагогіка; classification; класифікація; project method; метод проєктів; role play; рольова гра; cluster; кластер; brainstorming; «мозковий штурм»